Compact Symmetric Objects. I. Toward a Comprehensive Bona Fide Catalog - Kiehlmann, S. (Institute of Physics, 2025)
Compact symmetric objects (CSOs) are jetted active galactic nuclei (AGN) with overall projected size <1 kpc. The classification was introduced to distinguish these objects from the majority of compact jetted AGN in centimeter-wavelength very long baseline interferometry observations, where the observed emission is relativistically boosted toward the observer. The original classification criteria for CSOs were (i) evidence of emission on both sides of the center of activity and (ii) overall size <1 kpc. However, some relativistically boosted objects with jet axes close to the line of sight appear symmetric and have been misclassified as CSOs, thereby undermining the CSO classification. This is because two essential CSO properties, pointed out in the original papers, have been neglected: (iii) low variability and (iv) low apparent speeds along the jets. As a first step toward creating a comprehensive catalog of “bona fide” CSOs, we identify 79 bona fide CSOs, including 15 objects claimed as confirmed CSOs here for the first time, that match the CSO selection criteria. This sample of bona fide CSOs can be used for astrophysical studies of CSOs without contamination by misclassified CSOs. We show that the fraction of CSOs in complete flux density limited AGN samples with S5GHz > 700 mJy is between (6.8 ± 1.6)% and (8.5 ± 1.8)%. © 2024. The Author(s). Published by the American Astronomical Society.